Sintering of ceramics based on YBa2CuxOy Synthesized by plasma dynamic method; 11th International Forum on Strategic Technology (IFOST 2016); Pt. 1 - Shanenkova Yu. L. Yuliya Leonidovna; Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Shanenkov I. I. Ivan Igorevich (New materials and nanotechnologies, 2016)
Title screen